What motivates individuals to use FinTech budgeting applications? Evidence from India during the covid-19 pandemic - Basri Savitha; Iqbal Thonse Hawaldar (Cogent Economics & Finance, 2022)
The purpose of the present study was to explicate the factors determining customers' intention to use budgeting apps since the outbreak of COVID-19 pandemic. A cross-sectional survey in South India was conducted to collect data from 285 FinTech users. The data were analyzed using partial least square regression to estimate path coefficients and the PROCESS macro technique to identify moderation effects. Firstly, app engagement and self-efficacy were found to have a positive effect on the intention to use budgeting apps. Secondly, individuals who use FinTech services less frequently and those who use it to pay for a variety of expenses were found to have a greater effect on usage intentions of customer engagement, perceived trust, and perceived ease of use. Therefore, customization, real-time suggestions, providing tools for data visualization, smart data insights, and artificial intelligence-based recommendations and advice would assist customers in prudence money management.
Keywords: 330; budgeting; consumer; covid-19; Engagement; expenses; FinTech; intention; pandemic; self-efficacy; trust